Marine Based Biomaterials in Dental Regeneration - Varghese, Dr. Mekha Grace; George V., Dr. Thomas; Thomas, Dr. Nebu George; Pyas, Dr. Alenya Mary; Maymol Francis, Dr. Arimboor (International Journal of Innovative Research in Medical Science, 2020)
The novel approach of tissue engineering aims at regenerating the functional alveolar or periodontal tissues through a series of key events that is modulated by the use of scaffolds, cells and signalling molecules. Many synthetic and natural polymers have been used as tissue engineering constructs so far with varying results in regeneration. Developing a biomaterial to replace the damaged tissue is of paramount importance for effective regeneration. Due to its rich biodiversity, marine environment yields structures with immense potential for biomedical application. These bio molecules offer many applications in cartilage and bone tissue engineering, dental tissue regeneration, wound healing and local drug delivery system. These substances are usually nontoxic, bio compatible and well tolerated by the body, which boost their efficacy for tissue engineering application. In this article, we are trying to brief the various marine based biomaterials used in dental regeneration, their possible sources and clinical applications.